KORELASI NILAI PRAKTIK PENGALAMAN LAPANGANKEPENDIDIKAN DENGAN TINGKATKESIAPANMENJADI GURUMAHASISWA PENDIDIKANTEKNIKBANGUNAN ANGKATAN 2014 UNIVERSITAS NEGERI PADANG - Syafni Rayuna; Dr. M. Giatman, MSIE (CIVED, 2019)
Abstract― this study aims to reveal the correlation of the value of Educational Field Experience Practices with the level of readiness to be a teacher of Building Engineering Education Students of the Class of Padang State University in 2014. This type of research is descriptive correlational research with a quantitative approach. The population in this study was the 2014 Building Engineering Education students who had completed PPLK with a total of 44 people. Sampling uses total sampling technique. The instrument used is a questionnaire that has been validated by the validator. Data were analyzed with the help of SPSS Version 17.0 for Windows. The results of the study showed that there was a strong and significant correlation between the value of the Practice Field Experience Education and the level of readiness to become a teacher of Building Engineering Education Students of the 2014 Padang State University. (r count (0.414)> r table (0.297). Keywords: Practice Value, PPLK, Readiness, Teacher Competence